Social Strata Differentials in Reproductive Behavior among Agricultural Families in the Krummhörn Region (East Frisia, 1720-1874) - Kai Willführ; Charlotte Störmer (Historical Life Course Studies, 2015)
In this paper, we investigate how the reproductive behavior of families in the historical Krummhörn region was affected by their social status and by short-term fluctuations in their socioeconomic conditions. Poisson and Cox regression models are used to analyze the age at first reproduction, fertility, the sex ratio of the offspring, sex-specific infant/child survival, and the number of children. In addition, we investigate how fluctuations in crop prices affected infant and child mortality and fertility using Cox proportional regression models. We also include information about the seasonal climate that may have had an effect on crop prices, as well as on infant mortality via other pathways. We find that the economic upper class produced more infants and had more children who survived to adulthood than the lower social strata. While the upper class did not have lower infant and child mortality than the lower class, they had more surviving children because of their shorter birth intervals and lower female age at marriage. Crop prices did not affect mortality or fertility before 1820. From 1820 onwards, high crop prices were associated with increased child (but not infant) mortality and with extended inter-birth intervals. We believe this period-sensitive response to changes in the crop price was the result of a social transition that took place during our study period, in which relations between the classes went from being based on communal “table fellowships” (Tischgemeinschaft) to being based on capitalist employer/employee arrangements.